2014
DOI: 10.1021/nn505338e
|View full text |Cite
|
Sign up to set email alerts
|

A Complementary Palette of NanoCluster Beacons

Abstract: NanoCluster Beacons (NCBs), which use few-atom DNA-templated silver clusters as reporters, are a type of activatable molecular probes that are low-cost and easy to prepare. While NCBs provide a high fluorescence enhancement ratio upon activation, their activation colors are currently limited. Here we report a simple method to design NCBs with complementary emission colors, creating a set of multicolor probes for homogeneous, separation-free detection. By systematically altering the position and the number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 53 publications
0
90
0
Order By: Relevance
“…31,38,42 Other emissively silent violet clusters transform into a suite of clusters with strong emission that spans the green to red spectral regions. 42 The diverse spectra of these successor clusters are simply dictated by the sequence of the 5′ cluster domains in the single-stranded sensor (black sequence in Figure 1). Collectively, these studies support the inherent stability of violet clusters with a range of single-stranded DNA hosts.…”
Section: ■ Discussionmentioning
confidence: 99%
“…31,38,42 Other emissively silent violet clusters transform into a suite of clusters with strong emission that spans the green to red spectral regions. 42 The diverse spectra of these successor clusters are simply dictated by the sequence of the 5′ cluster domains in the single-stranded sensor (black sequence in Figure 1). Collectively, these studies support the inherent stability of violet clusters with a range of single-stranded DNA hosts.…”
Section: ■ Discussionmentioning
confidence: 99%
“…8,9,[33][34][35][36] Yeh, Martinez, Werner, and co-workers have carried out investigations on DNA detection probes with a greater focus on guanine bases. 12,23,[37][38][39] In addition to the experimental work, theoretical investigations have also been performed on DNA-AgNCs by several groups. Gwinn and coworkers have studied the binding of DNA bases (adenine, cytosine, guanine, and thymine) with neutral silver clusters Ag n (n=1-6) and the absorption spectra of these complexes using density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…This could be because AuNCs contract the DNA strand through nucleobase coordination, which results in a condensed and compact structure. Similarly, Obliosca et al 40 used SEC to determine the size of DNA-stabilized silver nanoclusters; they revealed that the retention time of 8 these nanoclusters was slightly slower than that of DNA strands. We also measured the hydrodynamic radius of A30-stabilized AuNCs to determine the impact of AuNC adducts on DNA shape.…”
Section: Resultsmentioning
confidence: 99%